PENGARUH GAYA KEPEMIMPINAN DAN LABOUR TURNOVER TERHADAP KINERJA KARYAWAN PT PERMODALAN NASIONAL MADANI MEKAAR AREA TANGERANG I - Chandella Wasilah; Irwansyah Irwansyah (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
Abstract. This study aims to determine the effect of leadership style and labour turnover on employee performance at PT Permodalan Nasional Madani (PNM) Mekaar Area Tangerang 1. The research method used is a quantitative approach with an associative type of research. Data collection techniques were carried out through the distribution of questionnaires to 57 respondents who are employees of PNM Mekaar. Data analysis was conducted using validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-test, F-test, and the coefficient of determination (R²) with the assistance of SPSS version 27. The results of the study indicate that partially, leadership style has a positive and significant effect on employee performance, with a t-value of 6.619 > t-table of 2.004 and a significance value of 0.009 < 0.05. Labour turnover also has a positive and significant effect on employee performance, with a t-value of 9.794 > t-table of 2.004 and a significance value of 0.008 < 0.05. Simultaneously, leadership style and labour turnover have a significant effect on employee performance, with an F-value of 4.292 > F-table of 3.168 and a significance value of 0.019 < 0.05. The coefficient of determination (R²) is 0.137, which means that both independent variables contribute 13.7% to employee performance, while the remaining 86.3% is influenced by other factors outside this study. Keywords: Leadership Style, Labour Turnover, Employee Performance.